An evaluation of the use and approaches of performance analysis within elite level english professional soccer clubs - Riley, P.; Littlewood, M.; Drust, B. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Performance analysis (PA) has been used in football for many years to review performance (Carling et al., 2005). The available literature fails to address vital questions relating to how components of PA affect the coaching process. There is a lack of data that relates to the relative effectiveness of the processes used within video-based PA that are required to adequately prepare players for competition, and to provide effective feedback both during and post performance. Methods The study utilised in-depth, semi structured interviews (Patton, 1980) to explore the use of performance and video analysis by performance analysts (n=10) working in the English Premier League (EPL). Data was analysed using inductive and deductive elements of content analysis (Patton, 1980; Glaser & Strauss, 1967). This provided a complete understanding of content, nature and reality of PA uses within football. Results & Discussion Five general dimensions emerged, `strategies and philosophies of PA`, providing an overview of the individuals uses for PA and ways it`s implemented. `Utilisation of current technology` which provides an overview of the technological infrastructure.`PA department structures`, bestows an insight into the roles, responsibilities and resources available. `Implementation of PA` highlights the main individuals that practice analysis and the key relationships formed during the process. `Future development of PA`, places a blueprint of the analyst`s vision for the future of PA. Conclusion The implementation of PA is prevalent in the football industry. This research provides evidence of the strategies that currently aid and are advancing the process of PA in EPL football clubs. The structure of analysis department is important to enhance the dynamic uses of PA in player and team improvement strategies. This study reveals the importance of PA within the coaching process and how this affects player and team development in EPL football clubs.